2021
DOI: 10.7759/cureus.12772
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach for Treatment of Woman With Absolute Uterine Factor Infertility: A Traditional Review of Safety and Efficacy Outcomes in the First 65 Recipients of Uterus Transplantation

Abstract: Malasevskaia et al. This is an open access article distributed under the terms of the Creative Commons Attribution License CC-BY 4.0., which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Following this first long-lasting case, experience in uterus transplantation has increased exponentially, and this has now become a reality rather than merely an experimental concept. In the writing of this manuscript, 65 such transplantations have been reported to date, and 22 infants have been successfully delivered, 4 from cadaveric donors 15 . The importance of deceased donor uterus transplantation lies in the fact zero harm occurs to the donor and in the possibility of retrieval of long vascular pedicles, thus improving the chances of vascular anastomosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following this first long-lasting case, experience in uterus transplantation has increased exponentially, and this has now become a reality rather than merely an experimental concept. In the writing of this manuscript, 65 such transplantations have been reported to date, and 22 infants have been successfully delivered, 4 from cadaveric donors 15 . The importance of deceased donor uterus transplantation lies in the fact zero harm occurs to the donor and in the possibility of retrieval of long vascular pedicles, thus improving the chances of vascular anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the writing of this manuscript, 65 such transplantations have been reported to date, and 22 infants have been successfully delivered, 4 from cadaveric donors. 15 The importance of deceased donor uterus transplantation lies in the fact zero harm occurs to the donor and in the possibility of retrieval of long vascular pedicles, thus improving the chances of vascular anastomosis. The first donor surgeries in Sweden lasted more than 10 hours, and the donors were transferred to ICU units after the procedures.…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36] Based on this experience, we established our diagnostic rejection criteria for the uterus in a cynomolgus macaque, 34 which partially referred to the grading system proposed by a Swedish group for monitoring rejection. 37 We believe that rejection of cellular and humoral components is more likely to develop in cynomolgus macaques, whose uteri may exhibit high levels of antigenicity compared with those of humans. 34,35 Another concern regarding UTx is whether a uterus with irreversible rejection should be removed.…”
Section: Rejectionmentioning
confidence: 99%
“…born after these procedures. 37,38 Thus, UTx research is circulating worldwide and is starting to be recognized as a feasible medical treatment for patients with UFI. However, UTx is not a commonly known medical technique in Japan.…”
Section: Activities and Preparations For Clinical Applicationmentioning
confidence: 99%
“…14 Additional clinical trials were initiated in the United States (Dallas, Cleveland, and Philadelphia), with the first live birth Baylor University Medical Center (BUMC) in Dallas, Texas, in 2016. 15 Reviews of the literature published in 2020 and 2021 identified 52 16 and 65 17 reported cases of UTx, respectively, and ~20 centers worldwide starting UTx research trials. 18 The first live birth following deceased-donor UTx was reported in 2018.…”
Section: Introductionmentioning
confidence: 99%